2001
DOI: 10.1300/j013v32n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Women's Psychological Well-Being in Indonesia

Abstract: This paper describes the development of a set of measures of women's psychological well-being in Indonesia, identifies meaningful clusters of women based on the well-being measures, and explores the sociodemographic factors associated with these well-being clusters. This is the first published study to measure psychological well-being among a large sample of Indonesians and the first to focus on women in that country. Rather than use standard measures of psychological well-being developed in Western nations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…In addition, scores for this item might have been affected by the social desirability response bias. According to religious teachings, Indonesians believe that they must have gratitude in life; thus, they do not want others to think that they are not satisfied with their lives (Eggleston et al, 2001). Personality traits such as psychological well‐being (vs. psychological distress) are said to be closely linked to social desirability, and because well‐being is clearly more desirable than distress, being asked about satisfaction may bias one toward socially desirable responses (Furr & Bacharach, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, scores for this item might have been affected by the social desirability response bias. According to religious teachings, Indonesians believe that they must have gratitude in life; thus, they do not want others to think that they are not satisfied with their lives (Eggleston et al, 2001). Personality traits such as psychological well‐being (vs. psychological distress) are said to be closely linked to social desirability, and because well‐being is clearly more desirable than distress, being asked about satisfaction may bias one toward socially desirable responses (Furr & Bacharach, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that religious practices were positively associated with Indonesians' quality of life (Yeo, 2014) as well as with stronger social cohesion (Yuniarti, 2006). Previous studies with the Indonesian population have shown that socioeconomic factors, such as income (Eggleston, Hardee, Irwanto, Poerwandari, & Severy, 2001), employment status (Rahayu, 2016), health (Eggleston et al, 2001), and gender differences (Landiyanto et al, 2011), are associated with well‐being. However, other studies have not fully supported these associations (e.g., Safarina, Mawarpury, & Sari, 2014; Sohn, 2013) and have highlighted the importance of other factors, such as religious values and principles, which influence attitudes, values, and people's interactions with each other (Primasari & Yuniarti, 2012; Yeo, 2014; Yuniarti, 2006).…”
Section: Indonesian Perspective Of Well‐beingmentioning
confidence: 99%
“…The measurement of well-beingin Indonesia mainly utilizes Psychological (Eggleston et al, 2001; to measure two distinctive bodies of well-being. Moreover, Maulana, Khawaja, and Obst (2019) developed the Indonesian Well-being scale, which measures dimensions, namely (1) Spirituality,…”
Section: Introductionmentioning
confidence: 99%